AtHD2D Gene Plays a Role in Plant Growth, Development, and Response to Abiotic Stresses in Arabidopsis thaliana - Han, Zhaofen; Yu, Huimin; Zhao, Zhong; Hunter, David; Luo, Xinjuan; Duan, Jun; Tian, Lining (Frontiers in Plant Science, 2016)
Abstracts: The histone deacetylases play important roles in the regulation of gene expression and the subsequent control of a number of important biological processes, including those involved in the response to environmental stress. A specific group of histone deacetylase genes, HD2, is present in plants. In Arabidopsis, HD2s include HD2A, HD2B, HD2C and HD2D. Previous research showed that HD2A, HD2B and HD2C are more related in terms of expression and function, but not HD2D. In this report, we studied different aspects of AtHD2D in Arabidopsis with respect to plant response to drought and other abiotic stresses. Bioinformatics analysis indicates that HD2D is distantly related to other HD2 genes. Transient expression in Nicotiana benthamiana and stable expression in Arabidopsis of AtHD2D fused with gfp showed that AtHD2D was expressed in the nucleus. Overexpression of AtHD2D resulted in developmental changes including fewer main roots, more lateral roots, and a higher root:shoot ratio. Seed germination and plant flowering time were delayed in transgenic plants expressing AtHD2D, but these plants exhibited higher degrees of tolerance to abiotic stresses, including drought, salt and cold stresses. Physiological studies indicated that the malondialdehyde (MDA) content was high in wild-type plants but in plants overexpressing HD2D the MDA level increased slowly in response to stress conditions of drought, cold, and salt stress. Furthermore, electrolyte leakage in leaf cells of wild type plants increased but remained stable in transgenic plants. Our results indicate that AtHD2D is unique among HD2 genes and it plays a role in plant growth and development regulation and these changes can modulate plant stress responses.